(untitled) (Journal of Hama University, 2024)
The research aimed to study the impact of monetary policy tools on changes in the consumer price index in Syria during the period 1990-2020, by studying the extent to which the consumer price index responds to shocks of changes in the exchange rate, interest rate, and Damascus stock market returns. The research relied on a set of statistical and inferential methods to test hypotheses, which consisted of collecting data from the Central Bank of Syria, the Ministry of Economy and Foreign Trade, and the Syrian Securities Commission, in addition to analyzing the data based on descriptive statistics, correlation tests, stability tests, and the structural VAR model. The results of the research showed the response of the Consumer Price Index to the variables of the study, as the response of the Consumer Price Index was directly to changes in the exchange rate, meaning that the current exchange rate policies do not contribute to controlling the rise in consumer prices. The CPI responds to the interest rate also within 10 months and negatively after 5 months. Consumer prices respond positively to changes in the Damascus Stock Exchange index.